A Religious Education Model Through the Habituation of Religious Values in Early Childhood - Hafidz, Nur; Aji Jauhari Ma’mun, Ahmad; Ayu Syifa, Wulan (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2025)
Religious education in early childhood has an important role in shaping the character and morals of children from an early age. This study aims to analyze the model of religious education applied through the habituation of religious values in RA Diponegoro 183 fast Gumelar. The method used in this study is qualitative-descriptive with a case study approach. Data were obtained through observation, interviews, and documentation. The results showed that the habituation of religious values is carried out through daily activities such as (1) spontaneous habituation through smiles, Greetings, greetings, reading thoyibah sentences; (2) habituation through prayer, Duha prayer, memorization of letters, songs and applause, and tahlilan: (3) exemplary habituation through read aloud Islamic story books and sayings please, sorry, and thank you; (4) programmed habituation to Islamic holidays and Banyumas birthdays. This model of religious education as a positive impact of religious habituation in instilling religious values, such as honesty, responsibility, and respect for others, which is reflected in children's daily behavior. This model of Education also involves the active role of parents and society in creating an environment that supports the religious development of children. In conclusion, the habituation of religious values in early childhood in RA Diponegoro 183 is a holistic and integrative approach in building the foundation of religious character from an early age.